Case report: Novel SCN4A variant associated with a severe congenital myasthenic syndrome/myopathy phenotype - Berghold, Veronika M.; Koko, Mahmoud; Berutti, Riccardo; Plecko, Barbara (Frontiers in Pediatrics, 2022)
We present a now 18-year-old female patient with a severe congenital myopathy phenotype, originally diagnosed as mitochondrial myopathy, however later revealed to constitute SCN4A-related myopathy based on genetic testing. After birth, floppiness, bradycardia and respiratory insufficiency ensued, and moderately reduced mitochondrial complex I activity was found in muscle tissue (tested at 3 weeks and 3 years of age). She was treated with riboflavin, carnitine, creatine and a ketogenic diet. At the age of 13 years, whole exome sequencing challenged the initial diagnosis by identifying two (compound heterozygous) SCN4A variants affecting the highly conserved pore region of the voltage-gated sodium channel NaV1.4: a known pathogenic loss of function (LOF) variant (c.4360C>T; p.(Arg1454Trp)) and a novel variant of uncertain significance (c.3615C>G; p.(Asn1205Lys)). For this novel variant, a LOF effect was predicted by in silico, clinical and functional evidence from paralog human sodium channels, and the variant was accordingly classified as likely pathogenic. The patient’s phenotype is in line with the few published cases of autosomal recessive SCN4A-related myopathy. There was limited benefit from treatment with salbutamol and acetazolamide, while pyridostigmine caused side effects at minor dose. This report highlights the importance of genetic testing in severe myopathies particularly in regard to treatment options and the value of paralog information in evaluating ion channel variations.